AB0161 Lymphatic Endothelial Progenitors Cells in Crohn's Disease and Spondyloarthropathy: A Link between Two Overlapping Diseases?. (10th June 2014) - Bandinelli, F.; Milia, A.F.; Lastraioli, E.; Manetti, M.; Rosa, I.; Arcangeli, A.; Matucci Cerinic, M.; Ibba Manneschi, L.
Abstract : Background: The lymphatic system has been proposed as the possible link between inflammatory bowel disease and spondyloarthropathy (SpA), which both display lymphedema and lymphangiogenesis. Nevertheless, the role of the lymphatic system in the connection between SpA and Crohn's disease (CD) still remains to be elucidated Objectives: To investigate the circulating levels of lymphatic endothelial progenitors cells (L-EPC) and their possible correlation with disease duration and activity indices in SpA, CD and SpA associated with CD (SC). Methods: Peripheral blood samples from patients affected by SpA (n=33), CD (n=25) and SC (n=20) and from 20 age- and sex-matched healthy controls were collected and used for quantification of circulating L-EPC. L-EPC were identified by FACS using anti-CD34 FITC-conjugated, anti-CD133 APC-conjugated and anti-VEGFR-3 PE-conjugated antibodies. L-EPC counts were reported as absolute number per 2x10 5 mononuclear cells and results were expressed as a percentage of total mononuclear cells. The correlation between L-EPC levels and disease duration (< or >10 years) and BASDAI for SpA or CDAI for CD was analyzed. Results: The number of L-EPC was significantly increased in CD (mean 4.69% ±9.9, p<0.004), SpA (9.24% ±11.2, p<0.005) and SC (5.42% ±4.5, p<0.01) patients compared with controls (2.0% ±1.89). In CD patients, a significant correlation was observed between L-EPC counts and disease duration, with significantly higher levels in earlier phases (p<0.03). L-EPC levels did not correlate either with BASDAI nor with CDAI. Conclusions: The increase of L-EPC levels in SpA, CD and SC observed in our study clearly indicate an active mobilization of lymphatic cell precursors. In particular, in CD, L-EPC mobilization may be related to the lymphangiogenesis process occurring in the first phases of the disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4297